Pengembangan Kompetensi Sosial - Sabrifha, Eli; Rahma, Talita; Alvandi, Ivan; Pebri, Novitra Susan (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
The development of social competence among educational administrative staff is a crucial aspect in supporting the effective operation of schools. Administrative staff are not only responsible for administrative tasks but also need adequate social skills to establish effective communication with teachers, students, parents, and other stakeholders. This study aims to analyze strategies for developing the social competence of educational administrative staff and the factors influencing it. The research employed a qualitative descriptive approach, collecting data through in-depth interviews, observations, and document analysis in several primary and secondary schools. The results indicate that social competence of administrative staff is influenced by interpersonal communication skills, empathy, teamwork, and conflict management. Systematic training programs, mentoring, and habitual professional interactions were found to effectively enhance their social abilities. Additionally, a supportive work environment and a collaborative school culture play a significant role in strengthening social competence.